Natural Resources Investment of Oil and Gas and Regional Development Impact on Community Empowerment - Ridwan Nyak Baik (Faculty of Geography, Universitas Gadjah Mada, 2015)
This study was done in Bekasi district, at West Java, Indonesia, with the aims to analyze the management of upstream activities (exploration and production) of oil and gas industry and its impact on improving the quality of infrastructure, the equal benefits proportion for the corporation, local government and society, and CSR programs that would affect the community empowerment. The analysis would be calculated based on the per capita income, the number of medical personals, and the number of teachers. Based on that calculation, this study analyzed the impact of oil and gas activities to the regional development of the area under this study. Analysis of regional development was calculated through number of industry in the area, the economic growth, and local government revenue that affects community empowerment in Bekasi.Analyzed by structural equation modeling (SEM), the results showed that: (1) management of upstream oil and gas activities in this area have a positive influence, but no significant effect on community empowerment; (2) management of upstream oil and gas activities have a significant positive impact on regional development; (3) regional development has a significant positive impact on community empowerment; (4) management of upstream oil and gas activities have a greater positive influence towards community empowerment through regional development, because of the multiplier effect of the development of the region.